A Comparison of Oxycodone and Alfentanil in Intravenous Patient-Controlled Analgesia with a Time-Scheduled Decremental Infusion after Laparoscopic Cholecystectomy. (20th September 2016) - Kwon, Young Suk; Jang, Ji Su; Lee, Na Rea; Kim, Seong Su; Kim, Young Ki; Hwang, Byeong Mun; Kang, Seong Sik; Son, Hee Jeong; Lim, So Young
Abstract : Background . Oxycodone, a semisynthetic opioid, has been widely used for acute and chronic pain. Objectives . The aim of this study was to compare the analgesic and adverse effects of oxycodone and alfentanil on postoperative pain after laparoscopic cholecystectomy. Methods . This was a prospective, randomized, double-blind study. A total of 82 patients undergoing laparoscopic cholecystectomy were randomly assigned to receive either oxycodone or alfentanil using intravenous patient-controlled analgesia (PCA). PCA was administered as a time-scheduled decremental continuous infusion based on lean body mass for 48 hours postoperatively. Patients were assessed for pain with a visual analogue scale (VAS), the cumulative PCA dose, adverse effects, sedation level at 1, 4, 8, 16, 24, and 48 hours postoperatively, and satisfaction during the postoperative 48 hours. Results . There were no significant differences (p < 0.05 ) between the two groups in VAS score, cumulative PCA dose, adverse effects, sedation level at 1, 4, 8, 16, 24, and 48 hours postoperatively, and satisfaction during the postoperative 48 hours. Conclusions . Our data showed that the analgesic and adverse effects of oxycodone and alfentanil were similar. Therefore, oxycodone may be a good alternative to alfentanil for pain management using intravenous PCA after laparoscopic cholecystectomy when used at a conversion ratio of 10 : 1. This trial is registered withKCT0001962 .